Experience of a single center with 472 vertebral augmentation surgery in 356 patients (Annals of Medical Research, 2021)
Aim: The objective of this study is to evaluate the clinical series of patients who underwent vertebral augmentation surgery in Neurosurgery department of Baskent University.Materials and Methods: The medical data stored in electronic and print files were retrospectively analyzed and patients operated in recent past were called for evaluation of outcome.Results: One clinical; pain relief and two radiologic, kyphotic angle and vertebral compression, criteria were used to evaluate the final outcome. The statistical analysis revealed that in all three parameters there was significantly important improvement in postoperative values. Procedure related complications were minor. No permanent neurologic deficit or mortality was seen.Conclusion: Both vertebral augmentation techniques are simple, effective and safe procedures provided that surgical indications are correct and surgical technique is properly carried out.